The effect of Computer Assisted Language Learning (CALL) intervention on knowledge of parts of speech of secondary school students / Nur Hazwani Ab. Ghani - Ab. Ghani, Nur Hazwani (2014)
Grammar is the foundation of language and mastering grammar might help learners to enhance their proficiency level in language. However, there are some conflicts in terms of attitudes and difficulty in mastering grammar. Thus, this study aims to investigate the effect of Computer Assisted Language Learning (CALL) intervention on knowledge of parts of speech of secondary school students. 60 secondary school students were selected to participate in this investigation. The researcher adopts a quasi-experimental design which includes a grammar pre-test followed by a period of CALL intervention. Grammar post-test and questionnaires were administered after the intervention programme. The pre-test and post-test scores and questionnaires were analyzed using descriptive and inferential statistics. The findings of this study indicate that the implementation of Computer Assisted Language Learning in teaching and learning grammar is beneficial to teachers and students. In general, Computer Assisted Language Learning improves students’ knowledge of parts of speech and promotes positive attitude in learning grammar. It also contributes to a different learning experience and allows learners to learn grammar at their own pace.